Isolasi Dan Identifikasi Senyawa Metabolit Sekunder Fraksi Etil Asetat Batang Tumbuhan Kratom (Mitragyna Speciosa) - Muhammad Akbar AS; Diana Eka Pratiwi; Pince Salempa (Jurusan Kimia FMIPA UNM, 2023)
ABSTRAK Penelitian eksplorasi ini bertujuan untuk mengisolasi dan mengidentifikasi senyawa metabolit sekunder ekstrak Fraksi Etil Asetat Batang Tumbuhan Kratom Mitragyna Speciosa Korth, meliputi tahapan fraksinasi, pemurnian dan identifikasi golongan serta spektrofotometer IR. Sampel penelitian ini merupakan fraksi E etil asetat batang tumbuhan kratom. Isolat yang diperoleh berupa serbuk kuning yang menunjukkan noda tunggal pada KLT system tiga eluen senyawa semi polar, hasil positif pada pereaksi Wagner dan Dragendorff didukung dengan identifikasi gugus fungsi pada spektrofotometer FTIR, bilangan gelombang 3338.78 cm-1 penunjukan gugus fungsi N-H yang didukung adanya puncak serapan pada 1290.38 cm-1 (vibrasi C-N), untuk serapan pada 2924.09 cm-1 dan 2854.65 cm-1 (C-H alifatik) yang didukung oleh adanya serapan pada 1462.04 cm-1 (CH2-) dan 1377.17 cm-1 (-CH3), Pada serapan bilangan gelombang 1705.07 cm-1 (C=O), pada daerah serapan 1510,26 cm-1 (C=C aromatic) dan pada daerah serapan 1136 cm-1 (C-O). Hasil pengujian golongan dan FTIR menunjukkan bahwa senyawa yang diperoleh merupakan golongan senyawa alkaloid.Kata Kunci : Kratom, Mitragyna Speciosa, Alkaloid ABSTRACTThis exploratory study aims to isolate and identify of secondary metabolic oompounds of ethyl acetate extract fraction of Kratom stem Mitragyna Speciosa Korth, including the steps of fractionation, purification and group identification by IR spectrophotometer. The sample of this study was the E ethyl acetate fraction of the kratom stems . Alkaloids obtained in the form of yellow powder which shows a single spot on the KLT system of three semi-polar compound eluents, positive results on Wagner and Dragendorff reagents are supported by the identification of functional groups on the FTIR spectrophotometer, wave number 3338.78 cm-1 indicates the NH functional group supported by the presence of an absorption peak at 1290.38 cm-1 (CN vibration), for absorption at 2924.09 cm-1 and 2854.65 cm-1 (aliphatic CH) which was supported by the presence of absorption at 1462.04 cm-1 (-CH2) and 1377.17 cm-1 (-CH3), The absorption wave number is 1705.07 cm-1 (C=O), the absorption area is 1510.26 cm-1 (C=C aromatic). The result of group testing and FTIR showed that the compounds obtained were alkaloid compoinds. Keywords : Kratom, Mitragyna Speciosa, AlkaloidThis exploratory study aims to isolate and identify of secondary metabolic oompounds of ethyl acetate extract fraction ofKratom stem Mitragyna Speciosa Korth, including the steps of fractionation, purification and group identification by IR spectrophotometer. The sample of this study was the E ethyl acetate fraction of the kratom stems . Alkaloids obtained in the form of yellow powder which shows a single spot on the KLT system of three semi-polar compound eluents, positive results on Wagner and Dragendorff reagents are supported by the identification of functional groups on the FTIR spectrophotometer, wave number 3338.78 cm-1 indicates the NH functional group supported by the presence of an absorption peak at 1290.38 cm-1 (CN vibration), for absorption at 2924.09 cm-1 and 2854.65 cm-1 (aliphatic CH) which was supported by the presence of absorption at 1462.04 cm-1 (-CH2) and 1377.17 cm-1 (-CH3), The absorption wave number is 1705.07 cm-1 (C=O), the absorption area is 1510.26 cm-1 (C=C aromatic). The result of group testing and FTIR showed that the compounds obtained were alkaloid compoinds. Keywords :Kratom, Mitragyna Speciosa, Alkaloid